Population proliferation and spread of Trichoderma spp. in soil under two different delivery systems (The Journal of Plant Protection Sciences, 2021)
Post application population proliferation (build up) and spread of Trichoderma spp., Trichoderma harzianum and  Trichoderma viride in three different types (sterilized, solarised and natural) clay loam soil at 50% water holding capacity  (pH 6.5) was studied both under laboratory and field conditions following two types of delivery systems, through organic  based (vermicompost + neem cake (90% + 10% w/w)) and seed based (sterilized wheat seed) inocula. The population  proliferation and spread of the antagonists were faster when they were applied through organic based inoculums over that  of seed based inoculums from the point of application. Similarly population proliferation and spread of the antagonist was  more rapid in sterilized soil followed by solarised soil and natural soil respectively. Among the two species of  Trichoderma, T. harzianum have spread faster than T. viride.
Keywords: Population proliferation; spread; delivery system; T. harzianum; T. viride; clay loam soil